2007
DOI: 10.1083/jcb.200707009
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin determines the migration behavior and turning frequency of metastatic cancer cells

Abstract: We have investigated the effects of inhibiting the expression of cofilin to understand its role in protrusion dynamics in metastatic tumor cells, in particular. We show that the suppression of cofilin expression in MTLn3 cells (an apolar randomly moving amoeboid metastatic tumor cell) caused them to extend protrusions from only one pole, elongate, and move rectilinearly. This remarkable transformation was correlated with slower extension of fewer, more stable lamellipodia leading to a reduced turning frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
171
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 51 publications
18
171
2
2
Order By: Relevance
“…This effect was similar to that of cells lacking Coronin 1B, an F-actin-binding protein that is localized to the leading edge of migrating fibroblasts (35). Cells that lacked PLEKHG3 had a longer shape, similar to that observed in cells lacking other well-known proteins, such as Cofilin (36) or WISp39 (37), that are localized to the leading edge. There was no significant difference in the actin structures of the H9 and PLEKHG3 −/− cells.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This effect was similar to that of cells lacking Coronin 1B, an F-actin-binding protein that is localized to the leading edge of migrating fibroblasts (35). Cells that lacked PLEKHG3 had a longer shape, similar to that observed in cells lacking other well-known proteins, such as Cofilin (36) or WISp39 (37), that are localized to the leading edge. There was no significant difference in the actin structures of the H9 and PLEKHG3 −/− cells.…”
Section: Discussionsupporting
confidence: 61%
“…There was no significant difference in the actin structures of the H9 and PLEKHG3 −/− cells. The elongated cell shape in the PLEKHG3 −/− cells might result from the enrichment of myosin II at the trailing edge of cells, which leads to antagonistic protrusion activity (38,39), or from an asymmetric localization of the Arp2/3 complex to the leading edge of the elongated cell (36). Here, we observed that PA-Rac1 led to the formation of lamellipodia, and PLEKHG3 was detected in the newly formed protrusion area on a characteristic time scale of ∼30 s. Closer observation showed the recruitment of PLEKHG3 at the newly formed actin filaments at the leading edge.…”
Section: Discussionmentioning
confidence: 99%
“…Cofilin regulates actin dynamics by severing actin filaments and sequestering the actin monomer from the pointed end of actin filaments. Though, once phosphorylated by LIMKs, cofilin can no longer bind to actin, resulting in increase of actin polymers, actin stress fiber formation and a reduction in cell mobility (Arber et al, 1998;Sidani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, severed filaments are the preferred substrate for dendritic nucleation by the Arp complex (8,9). Localized induction of actin polymerization and the formation of branched actin networks constitute the basis for membrane protrusion and cell motility (2,10,11). In line with an upstream regulatory role in the control of these processes, PKD1 and -2 are also capable of binding to F-actin in vitro (1).…”
mentioning
confidence: 99%